Non-Radiographic Risk Factors Differentiating Atypical Lipomatous Tumors from Lipomas - Bird, Justin E.; Morse, Lee Jae; Feng, Lei; Wang, Wei-Lien; Lin, Patrick P.; Moon, Bryan S.; Lazar, Alexander J.; Satcher, Robert L.; Madewell, John E.; Lewis, Valerae O. (Frontiers in Oncology, 2016)
Purpose: To determine non-radiographic risk factors differentiating atypical lipomatous tumors (ALTs) from lipomas. Methods: All patients with deep-seated lipomatous tumors of the extremities treated from January 2000 to October 2010 were retrospectively reviewed. Factors reviewed included age, gender, tumor location, size, histology, local recurrence, dedifferentiation and metastasis. Multivariate logistic regression models were used to evaluate the effects of patient characteristics on ALT status. Results: Ninety-four lipomas and 46 ALTs were included. Patients with an ALT were older (median: 60.5 years versus 55 years). Lipomas were evenly distributed between upper (48.9%) and lower extremities (51.1%), whereas ALTs predominately involved the lower extremities (91.3%). Median ALT size (22cm) was greater than lipomas (10cm), p<0.0001. One lipoma (1.04%) recurred at 77 months and 5 ALTs (10.9%) recurred at an average of 39 months (19 to 64 months). Two ALTs originally treated with wide resection recurred with a dedifferentiated component and were treated with wide re-excision and chemotherapy. No metastases or tumor-related deaths occurred in either group at the time of last follow-up. Patients older than 60-years, tumors greater than 10cm, or thigh location, were more likely to be diagnosed with an ALT (p<0.05). Conclusion: Lipomatous tumors were more likely to be atypical lipomatous tumors when the tumor was at least 10 cm in size, located in the thigh, or found in patients that were 60 years of age or older. These risk factors may be used to guide management and surveillance strategies when lipomatous tumors do not display characteristic radiographic features.